Respon GA3 Terhadap Induksi Tunas Mikro Tanaman Karet (Hevea brasiliensis (Muell). Arg) - Larosa Harahap; Luthfi Aziz Mahmud Siregar; Diana Sofia Hanafiah (Universitas Sumatera Utara, 2016)
The aim of the research was to know effect of GA3 to rubber plant in micro shoot formation. The research was conducted at the rubber plant microcutting labortory PT Perkebunan Nusantara III Kebun Gunung Pamela, Tebing Tinggi, North Sumatera, Indonesia from April 2015 to Juli 2015. The Completely randomize design was used with two factors,i.e.:the addition of GA3 (GA3 0 mg/l; GA3 0.5 mg/l; GA3 1 mg/l; GA3 1.5 mg/l) and the immersion of nodes (GA3 0 mg/l; GA3 5 mg/l; GA3 10 mg/l; GA3 15 mg/l) with seven replications. The result showed that addition of 0.5 mg/l GA3 of significantly affected the percent of shoot emergence but no significantly different age of shoot emergence and immersion of nodes of 0 mg/l significantly affected the percent of shoot emergence but no significantly different age of shoot emergence and the interraction that addition of 0.5 mg/l GA3 and immersion of nodes significant affected the percent of shoot emergence on age of shoot emergence but no significantly different.Keywords : rubber, micro shoot, addition of GA3, immersion of nodesThe aim of the research was to know effect of GA3 to rubber plant in micro shoot formation. The research was conducted at the rubber plant microcutting labortory PT Perkebunan Nusantara III Kebun Gunung Pamela, Tebing Tinggi, North Sumatera, Indonesia from April 2015 to Juli 2015. The Completely randomize design was used with two factors,i.e.:the addition of GA3 (GA3 0 mg/l; GA3 0.5 mg/l; GA3 1 mg/l; GA3 1.5 mg/l) and the immersion of nodes (GA3 0 mg/l; GA3 5 mg/l; GA3 10 mg/l; GA3 15 mg/l) with seven replications. The result showed that addition of 0.5 mg/l GA3 of significantly affected the percent of shoot emergence but no significantly different age of shoot emergence and immersion of nodes of 0 mg/l significantly affected the percent of shoot emergence but no significantly different age of shoot emergence and the interraction that addition of 0.5 mg/l GA3 and immersion of nodes significant affected the percent of shoot emergence on age of shoot emergence but no significantly different.Keywords : rubber, micro shoot, addition of GA3, immersion of nodes